2022
DOI: 10.1108/jpbm-06-2021-3534
|View full text |Cite
|
Sign up to set email alerts
|

When is sustainability an asset? The interaction effects between the green attributes and product category

Abstract: Purpose Products that espouse environmental ethical principles have received increasing attention in recent years. However, one key barrier against sustainable consumption is that green attributes could result in consumer’s expectation of decreased product physical performance. This study aims to investigate how green attributes existing in different product categories affect consumer purchase intention. Design/methodology/approach Two experimental studies were conducted to test the hypotheses. Study 1 provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…External factors include green communication strategies (Lin et al , 2021), positioning strategies (Gong et al , 2021), attribute promotion strategies (Gong et al , 2022) and eco-labeling (Taufique et al , 2017). By enhancing green transparency and meeting consumers’ green competence needs, companies can strengthen consumer attachment to green brand attachment and foster greater brand loyalty (Lin et al , 2021).…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…External factors include green communication strategies (Lin et al , 2021), positioning strategies (Gong et al , 2021), attribute promotion strategies (Gong et al , 2022) and eco-labeling (Taufique et al , 2017). By enhancing green transparency and meeting consumers’ green competence needs, companies can strengthen consumer attachment to green brand attachment and foster greater brand loyalty (Lin et al , 2021).…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…They can also improve consumers’ perception of warmth and competence by emphasizing the brand’s green functional and emotional positioning, which ultimately boosts purchase intention (Gong et al , 2021). Furthermore, companies can foster positive purchase intention by promoting green peripheral attributes in functional products and green core attributes in hedonic products (Gong et al , 2022).…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…Lin & Niu, 2018), self‐responsibility and moral identity (Peloza et al, 2013), and habits (White et al, 2019) are predictors of consumers' choosing environment‐friendly products. In terms of product‐related factors, products' symbolic meaning (conspicuous vs. nonconspicuous green products, Yao et al, 2020), price and quality attributes (Biswas & Roy, 2015; Y. Li et al,2016; Rana & Paul, 2017), and type (utilitarian vs. hedonistic green products, S. Gong et al, 2022) have been shown to influence consumer decisions. Finally, others' perceptions and ideas can influence green consumption (He et al, 2015; Shi & Jiang, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Previous research suggest that goals consumers pursue when purchasing products significantly influence their mental representational state (Petty and Wegener, 1998; Ligas, 2000). Depending on the goals they help consumers achieve products can be utilitarian or hedonic (Cervellon and Carey, 2014; Gong et al , 2022; Luchs and Kumar, 2017). Utilitarian products are mostly purchased for objective problem-solving reasons, while hedonic products serve subjective desire-pursuing purposes (Chitturi et al , 2008).…”
Section: Introductionmentioning
confidence: 99%